The Effect of Income and Financial Literacy on the Consumptive Behavior of Shopee Paylater Users in Generation Z in Bandar Lampung City - Setiawati, Dini Eka; Alam, Iskandar Ali (LPPPIPublishing, 2023)
The objective of this research is to examine the influence of income and financial literacy on the consumtive behavior of Shopee Paylater customers from Generation Z in Bandar Lampung City. The study used a quantitative methodology, focusing on the generation Z population residing in the city. The collection of primary data was the dissemination of online questionnaires to a sample of 100 respondents who were both users of Shopee Paylater and within the age range of 18-25 years. “The process of selecting samples is conducted using non-probability sampling techniques, with a particular emphasis on purposive sampling. Data analysis was performed using multiple linear regression models to explain the relationship between independent variables (income and financial literacy) to dependent variables (consumptive behavior). Statistical software such as SPSS 29.0 or Excel is used for data analysis. The tests performed include descriptive analysis, classical assumption tests, t tests, F tests. The level of achievement of respondents shows that variable X1 income is included in criteria neutral with a percentage of 68.45, for variable X2 financial literacy criteria neutral with a percentage of 65.50% and variable consumptive behavior Y criteria neutral with a percentage of 63.04%. The results of the analysis concluded that partially, income (X1) has a positive influence on consumptive behavior (Y). Financial literacy (X2) partially has a positive influence on consumptive behavior (Y). In addition, simultaneously, income and financial literacy have an impact on the consumptive behavior of generation Z Shopee Paylater users in Bandar Lampung City.